Neuronal Responses to a Postural Dual-Task With Differential Attentional Prioritizations: Compensatory Resource Allocation With Healthy Aging. (28th June 2018) - Yu, Shu-Han; Hwang, Ing-Shiou; Huang, Cheng-Ya
Abstract: Objectives: Restricted central processing in older adults prevents optimization of a dual task with a flexible prioritization strategy. This study investigated the neural mechanisms of task-priority in young and older adults when performing a posture-motor dual-task. Method: Sixteen healthy young and 16 older adults performed a force-matching task on a mobile-platform under posture-focus (PF) and supraposture-focus (SF) conditions. The platform movement, force-matching performance, and event-related potentials in the preparatory period were recorded. Results: For the elders, the postural stability and force-matching accuracy using the PF strategy were inferior to those using the SF strategy; whereas, the dual-task performances of the young adults were less affected by the prioritization. Only the elders exhibited the P1 wave, with the PF strategy associated with a smaller P1 and larger P1 than the SF strategy in the sensorimotor-parietal and right frontotemporal areas, respectively. The PF strategy also led to a larger P2 wave in the right frontotemporal area of elders, but a greater P2 wave in the sensorimotor-parietal area of young adults. Discussion: For both prioritization strategies, older adults entailed a longer preparatory process than younger adults. Dual-task performance of older adults was more vulnerable to PF strategy, underlying compensatory resource allocation in the preparatory period for resolution of dual-task interference due to degenerated frontal function.